Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1097/ijg.0000000000000994
|View full text |Cite
|
Sign up to set email alerts
|

Provider Agreement in the Assessment of Glaucoma Progression Within a Team Model

Abstract: Fair to moderate agreement levels were found among providers in their assessment of glaucoma progression, suggesting that a team approach to glaucoma management may be effective. Further work is needed to investigate ways to optimize consistency within the glaucoma team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…These articles compared the performance of the non-medical staff with that of the GE, or compared SC in general with StC [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. All articles concentrated on an actual clinic performing SC, including the glaucoma follow-up unit in the Rotterdam Eye Hospital (SC-GFU) [ 36 , 37 , 38 ], the Mayo clinic (SC-MC) [ 33 , 34 , 35 ], the Moorfield Eye Hospital (SC-MEH) [ 40 , 42 ], the Queen’s medical centre (SC-QMC) [ 39 ], the Stable Glaucoma Clinic in New Zealand (SC-SGC) [ 43 ], the Glaucoma Management Clinic in Australia (SC-GMC) [ 44 ] and one established between the Royal Victorian Eye & Ear Hospital and the Australian College of Optometry (SC-RVAC) [ 41 ]. The corresponding StC clinic in each hospital is referred as “StC—(name of the corresponding clinic/hospital)”.…”
Section: Results Of Shared Care Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…These articles compared the performance of the non-medical staff with that of the GE, or compared SC in general with StC [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. All articles concentrated on an actual clinic performing SC, including the glaucoma follow-up unit in the Rotterdam Eye Hospital (SC-GFU) [ 36 , 37 , 38 ], the Mayo clinic (SC-MC) [ 33 , 34 , 35 ], the Moorfield Eye Hospital (SC-MEH) [ 40 , 42 ], the Queen’s medical centre (SC-QMC) [ 39 ], the Stable Glaucoma Clinic in New Zealand (SC-SGC) [ 43 ], the Glaucoma Management Clinic in Australia (SC-GMC) [ 44 ] and one established between the Royal Victorian Eye & Ear Hospital and the Australian College of Optometry (SC-RVAC) [ 41 ]. The corresponding StC clinic in each hospital is referred as “StC—(name of the corresponding clinic/hospital)”.…”
Section: Results Of Shared Care Studiesmentioning
confidence: 99%
“…Agreement between GEs and optometrists on IOP was evaluated in two studies [ 33 , 40 ] and was found to be good. Banes et al [ 40 ] noted that optometrists tended to record lower IOP, but differences were small.…”
Section: Results Of Shared Care Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 The definition and diagnosis of glaucoma, although 'classically' understood, 9 remains nebulous and agreement of the interpretation of test results within and between clinicians -optometrists and ophthalmologistsremains variable. [10][11][12][13][14][15][16][17] Adjunctively to this, unusually, there is also the proposed issue of over-treatment or overdiagnosis of glaucoma. 18,19 Large-scale clinical trials have frequently reported a subset of patients who almost never progress even without treatment.…”
mentioning
confidence: 99%